BSHI guideline: HLA matching and donor selection for haematopoietic progenitor cell transplantation. (10th February 2021) - Little, Ann‐Margaret; Akbarzad‐Yousefi, Arash; Anand, Arthi; Diaz Burlinson, Natalia; Dunn, Paul P. J.; Evseeva, Irina; Latham, Katy; Poulton, Kay; Railton, Dawn; Vivers, Sharon; Wright, Paul A.
Abstract: A review of the British Society for Histocompatibility and Immunogenetics (BSHI) Guideline 'HLA matching and donor selection for haematopoietic progenitor cell transplantation' published in 2016 was undertaken by a BSHI appointed writing committee. Literature searches were performed and the data extracted were presented as recommendations according to the GRADE nomenclature.